Integrating Traditional and Modern Leadership in Education: Strategies to Increase Effectiveness - Zainal Abidin; Faishol Ahmad; Ahmad Qusairi; Fadhel Mubarak (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2025)
Community-based education management in Indonesia, especially in environments with strong cultures such as Madin Al-Hidayah Pasuruan, faces challenges in integrating traditional and modern leadership. The main problem is how to combine these two paradigms harmoniously to improve the effectiveness of management and sustainability of educational institutions. This study aims to analyze the process of integrating traditional and modern leadership in Madin Al-Hidayah and identify factors that influence its success. The approach used is qualitative with a case study, through primary data collection from in-depth interviews with 26 respondents including leaders, teachers, and community leaders, as well as secondary data from related documents and literature. Data were analyzed using thematic methods to identify patterns and relationships that support interpretation. The results of the study indicate that the success of integration depends on cultural sensitivity, leader capacity, and adaptive communication strategies. Strategies that successfully implement a gradual and participatory approach successfully strengthen the relationship between customary power and innovative principles of modern leadership. These findings suggest the need for capacity training, active community involvement, and the development of contextual and harmonious leadership models. This study contributes to the development of theory and practice of culture-based education management in Indonesia, while opening up opportunities for in-depth studies on leadership transformation in customary-based communities.